2020
DOI: 10.1101/2020.07.09.195560
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Solvent quality and chromosome folding inEscherichia coli

Abstract: SummaryAll cells must fold their genomes, including bacterial cells where the chromosome is compacted into a domain-organized meshwork called nucleoid. Polymer conformation depends highly on the quality of the solvent. Yet, the solvent quality for the DNA polymer inside cells remains unexplored. Here, we developed a method to assess this fundamental physicochemical property in live bacteria. By determining the DNA concentration and apparent average mesh size of the nucleoid, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 166 publications
(265 reference statements)
0
7
0
Order By: Relevance
“…Ribosomes alone occupy ∼20% of that volume (Delarue et al, 2018). Biophysical studies revealed that these constituents form a porous, visco-elastic material that allows diffusion of small molecules but impedes movement of larger particles (Luby-Phelps et al, 1986; Moeendarbary et al, 2013; Xiang et al, 2020), and molecular simulations show a high density of macromolecules jostling and colliding from diffusive motion. (Mcguffee and Elcock, 2010; Yu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Ribosomes alone occupy ∼20% of that volume (Delarue et al, 2018). Biophysical studies revealed that these constituents form a porous, visco-elastic material that allows diffusion of small molecules but impedes movement of larger particles (Luby-Phelps et al, 1986; Moeendarbary et al, 2013; Xiang et al, 2020), and molecular simulations show a high density of macromolecules jostling and colliding from diffusive motion. (Mcguffee and Elcock, 2010; Yu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“… 13 , 14 , 17 Furthermore, the cytoplasm in bacteria is a poor solvent for DNA, causing the spontaneous compaction and formation of domain-like structures. 10 Lastly, the DNA polymer itself as well as the surrounding cytoplasm were found to exhibit confinement-induced glassy dynamics, both in bacteria 11 and in human cells. 12 , 15 , 16 …”
Section: An Overview Of Chromosome Building Blocksmentioning
confidence: 99%
“…(ii) Distribution of ribosomes (that act as crowders) in E. coli from cryo-electron tomograms. Adapted with permission from ref ( 10 ). Copyright 2020 Xiang et al .…”
Section: An Overview Of Chromosome Building Blocksmentioning
confidence: 99%
See 2 more Smart Citations